Silver award at the Pygmalion Awards - Poster Advertising - Creative Club of Cyprus member of the ADCE (Europe) - Panayides, Angelos (My University, 2026)
The award was received by the Creative Club of Cyprus member of the Art Directors Club of Europe (ADCE).
Keywords: Arts and entertainment